Student management in improving the quality of graduates at MTs islamiyah Barbaran - Siti Maisyaroh Nasution; Ali Yusron; Marwah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Student management is the arrangement of all student activities related to the proces from the time students enter to the time they leave. Student management activities are part of on educational institution. Student management activities are also an important part that must be constidered in its implemention. This paper raises the title of student answer the question of haw student management improves the quality graduates at MTs Islamiyah Barbaran and what are the supporting and inhibiting factors in improving the quality of graduates. The purpose of this reseacrh is do describe and analyze the role of student management in improving the quality of graduates at MTs Islamiyah Barbaran. Student management is an important part of educational management, encompassing planning, organizing, implementing, and supervising all student activities throughout the educational process. Through a qualiative approach, data was collected through observation and interviews with the principal, the deputy principal for curriculum, the deputy principal for student affairs, administration, and students. The results show that student management at MTs Islamiyah Barbaran has been implemented systematically, starting from the new student admission process, character development, academic guidance, to the management of guidance and counseling. These efforts contribute to improving academic achievement, discipline, and the readiness of graduates to continue their education to a higher level. With effeictive management, the madrasag is able to produce graduates who excel not only in cognitive aspects, but also in affective and pysychomotoror aspects.